2006
DOI: 10.1017/s1355617706060498
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and cognitive predictors of long-term psychosocial outcome following traumatic brain injury

Abstract: Demographic factors and cognitive impairment have been found previously to have associations with outcome after brain injury. Kendall and Terry (1996) suggest that preinjury psychosocial functioning, neurological factors, and cognitive impairment have a direct relationship with multidimensional psychosocial adjustment, but that cognitive impairment also has an indirect relationship by means of the mediation of appraisal and coping variables. The aim of this study was to explore these theoretical relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
85
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 40 publications
6
85
1
1
Order By: Relevance
“…On the other hand, Hoofien et al (2002) reported that injury severity, as measured by length of coma, was only predictive of psychiatric symptoms, accounting for 16% of the variance in this area. Wood and Rutterford (2006a) found that PTA duration was not significantly associated with most outcome measures, except for satisfaction with life, accounting for just 7.8% of variance. They suggested that the predictive power of injury severity may decline over time.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…On the other hand, Hoofien et al (2002) reported that injury severity, as measured by length of coma, was only predictive of psychiatric symptoms, accounting for 16% of the variance in this area. Wood and Rutterford (2006a) found that PTA duration was not significantly associated with most outcome measures, except for satisfaction with life, accounting for just 7.8% of variance. They suggested that the predictive power of injury severity may decline over time.…”
Section: Introductionmentioning
confidence: 82%
“…Regarding the influence of demographic variables, studies by Dawson and Chipman (1995), Hoofien et al (2002), Johnson (1998), Tate et al (2005), and Wood and Rutterford (2006a) have found no significant association between either age or gender and outcome. However, higher preinjury education has been associated with better long-term outcome in employment, social functioning, and community integration, both alone and in combination with injury severity, age, gender, and0or relationship status (Dawson & Chipman, 1995;Hoofien et al, 2002;Wood & Rutterford, 2006a).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations